Essays - Dickinson, G. Lowes (Goldsworthy Lowes), 1862-1932, author.
1 online resource.
Keywords: The Collected Works of G. Lowes Dickinson reissues nine titles from Dickinson's impressive oeuvre. The titles in question cover a range of topics, from Plato and the Greek view of life to civilisation and the causes of war.